Simulation of Fire Emergency Evacuation in a Primary School Based on Pathfinder Software - Mahdi Safari; Reza Afkhami; Mohammad Amerzadeh; Vida Zaroushani (Buildings)
(1) Background: In Iran, burn injuries are the second leading cause of death among children, surpassed only by traffic accidents. This study aims to simulate fire emergency evacuations in an elementary school using Pathfinder software, focusing on identifying architectural factors that influence evacuation efficiency. Children are particularly vulnerable in emergencies due to their limited understanding of danger and tendency to panic, making the development of effective evacuation strategies essential for their safety. (2) Methods: We analyzed the emergency evacuation of 522 occupants at a selected elementary school in Qazvin City, Iran. Using Pathfinder 2021 software, we examined various evacuation scenarios, including evacuation density, traffic patterns on different routes, and flow at exits. We calculated the Required Safe Egress Time (RSET) and Available Safe Egress Time (ASET) from the simulation data. Data collection involved a comprehensive assessment of the school’s geometric characteristics, as well as the demographic and anthropometric profiles of the occupants. (3) Results: The simulations revealed a total evacuation time of 386 s, with an ASET of 180 s. The average passenger flow rate was only 1.35 persons per second, indicating a slow evacuation process. Our findings highlighted that specific architectural features, such as classroom size and door dimensions, significantly affect evacuation times. Additionally, when simulating an evacuation with 170 fewer students, the total evacuation time decreased by 128 s, suggesting that adhering to recommended class size standards can enhance evacuation efficiency. Notably, the RSET consistently exceeded the ASET (180 s) across all simulations. (4) Conclusions: This research deepens our understanding of school evacuation dynamics and underscores the need for improved architectural designs and safety protocols to protect vulnerable populations, especially children. Future studies should focus on implementing targeted interventions based on these findings to mitigate risks associated with school fires. Additionally, the results indicate that installing automatic fire alarms and extinguishing systems, along with conducting regular emergency evacuation drills for students, could significantly reduce RSET.